Plants control soil gas exchanges possibly via mucilage - Haupenthal, Adrian; Brax, Mathilde; Bentz, Jonas; Jungkunst, Hermann F.; Schützenmeister, Klaus; Kroener, Eva (Journal of plant nutrition and soil science, 2021)
Background: Gaseous matter exchanges in soil are determined by the connectivity of the pore system which is easily clogged by fresh root exudates. However, it remains unclear how a hydrogel (e.g., mucilage) affects soil pore tortuosity and gas diffusion properties when drying. Aims: The aim of this viewpoint study is to extend the understanding of gas exchange processes in the rhizosphere by (a) relating it to the patterns formed by drying mucilage within pore space and (b) to give a concept of the effect of drying mucilage on soil gas diffusivity using the combination of experimental evidence and simulations. Methods: To describe the effect of mucilage on soil gas exchanges, we performed gas diffusion experiments on dry soil–mucilage samples and took images of glass beads mixed with mucilage to visualize the formation of mucilage after drying, using Environmental Scanning Electron Microscopy. Finally, we set up simulations to characterize the geometric distribution of mucilage within soil during the drying process. Results: Experiments of gas diffusion show that mucilage decreases gas diffusion coefficient in dry soil without significantly altering bulk density and porosity. Electron microscopy indicates that during drying mucilage forms filaments and interconnected structures throughout the pore space reducing gas phase connectivity. The evolution of these geometric structures is explained via pore scale modelling based on identifying the elastic strength of rhizodeposition during soil drying. Conclusion: Our results suggest that releasing mucilage may be a plant adaption strategy to actively alter gas diffusion in soil.